Challenging 'definite article' as a comparative concept: The case of Mopan Maya. (May 2022) - Contini-Morava, Ellen; Danziger, Eve
Abstract: The concept of 'definite article' is an example of a conceptual primitive intended to be universally applicable for typological comparison. We demonstrate that the article a (ART) in Mopan (Mayan) does not encode the concept of definiteness, even though some of its uses conform with conventional understandings of this concept. We argue instead that ART, together with its associated predicate, forms a constituent that is construed as an entity, and thus designated for use as a nominal. Although marking with ART explicitly promotes status as a nominal, bare nominals are nevertheless possible in Mopan. However, unlike languages in which bare nominals occur in semantically or syntactically predictable contexts, this is not true of Mopan ART. We use quantitative data to show that use vs. non-use of ART with a nominal correlates with relative foregrounding of its referent in discourse. We propose that this pragmatic function explains past misrecognition of ART as an encoder of definiteness. We question the usefulness of 'definite article' as a universally applicable primitive and suggest that proposals of putatively universal primitives for cross-linguistic study may be weakened by failure to consider language-particular communicative needs, and/or pragmatic factors in use of forms. Highlights: The Mopan Maya article (ART) does not encode definiteness. We challenge 'definite article' as a typological primitive. Rather than encoding definiteness, ART encodes explicit designation of the following intransitive predication as an entity. Presence/absence of ART correlates with discourse salience; this pragmatic factor may underlie prior misrecognition as definite. Comparative concepts based on 'overlap' or polysemy diagnostics may misidentify language-particular meanings.